Impact of feed management on diet selectivity, performance, and economic return of feedlot lambs - de Souza, Daniel Martins [UNESP]; Costa, Ciniro [UNESP]; de Lima Meirelles, Paulo Roberto [UNESP]; de Castilhos, André Michel [UNESP]; Pariz, Cristiano Magalhães [UNESP]; Barros, Juliana da Silva [UNESP]; Furlan, Lucas Bravim [UNESP] (FapUNIFESP (SciELO), 2025)
The development of feeding strategies can improve production indices and financial returns in livestock systems. This study evaluated the effects of bunk management and feeding adjustment intervals on selectivity, performance, feed refusals, and economic return of feedlot lambs. Sixty crossbred White Dorper x Ile de France lambs (27.89 kg ± 3.71 kg) at approximately 90 days of age (± X days) were assigned to treatments based on body weight, allocated to one of twenty pens (five pens, four blocks, and three animals per pen). The experiment consisted of a randomized block design with a 2 x 2 factorial arrangement and treatments consisting of bunk management for feed refusals of 5-10% and 10-15% and two feeding adjustment intervals every two or three days. Bunk management for feed refusals of 5-10% led to a higher intake of particles smaller than 4 mm (50.73% and 49.37%, P = 0.0022), lower feed waste (0.220 and 0.246 kg DM/day, P < 0.0001), and higher dry matter intake (DMI) (3.775 kg/day, P = 0.0440). Feeding adjustment performed every three days showed higher feed supply (3.966 kg and 3.863 kg DM/day, P = 0.0005) and higher DMI both in kg/day (3.775 kg/day, P = 0.0004) and body weight (3.334% and 3.233% of LW, P = 0.0150). Management with feed refusals of 5-10% and a feeding adjustment interval every three days presented the highest revenue (R$ 688.15) and the lowest cost per kilogram (R$ 2.57). Therefore, bunk management for feed refusals of 5-10% and feeding adjustment intervals every three days was the most viable strategy.
Impacto do manejo alimentar na seletividade da dieta, desempenho e no rendimento econômico de cordeiros confinados
Keywords: feeding behavior; feeding management; feedlot; Ovis aries